Characterization and Evaluation of Reservoir Micro-Pore Structure in Unconventional Oil and Gas Reservoir Development - Yan, Yongfei (Scientific Journal of Technology, 2025)
Unconventional oil and gas reservoirs have the typical characteristics of "low porosity, low permeability and strong heterogeneity", and their microscopic pore structure is the core factor to control the occurrence, migration and development efficiency of oil and gas. This paper systematically summarizes the technical system and theoretical method of characterization and evaluation of reservoir micro-pore structure. It is pointed out that at present, there are challenges such as difficulty in multi-scale data fusion, insufficient data heterogeneity and model adaptability, and interference of mineral composition, and the data difference between different technologies can reach more than 30%. The future development direction lies in the development of "macro-micro-nano" multi-scale technology chain, the integration of artificial intelligence algorithms to achieve seamless data connection, the promotion of four-dimensional dynamic monitoring technology, the establishment of standardized evaluation models, and the expansion to cross-cutting fields such as CO₂ storage, and the construction of a "high-precision-full-scale-dynamic" comprehensive characterization system, which provides theoretical support for the efficient development of unconventional oil and gas.